Development of a cost effective passive sampler to quantify the particulate matter depositions on building materials over time. (20th September 2020) - García-Florentino, Cristina; Maguregui, Maite; Carrero, Jose Antonio; Morillas, Héctor; Arana, Gorka; Madariaga, Juan Manuel
Abstract: Air pollution represents a serious risk for the preservation of open-air Cultural Heritage. The increased on Particulate Matter contamination may contribute to trigger the sulphating process of porous building materials and to add new ions, which may react and change the original composition of the materials. Because of this, the knowledge of PM composition near monuments or buildings over time is becoming an important issue in conservation strategies. In this work, a simple and cost-efficient passive sampler is proposed to quantify the PM being deposited over building material surfaces per area and time of exposure. The passive sampler described in this work, consisting on retainers specially designed for XRF analysis, is used for the first time as a simple way for characterising the surrounding atmospheric contamination caused by PM, without the need of other commonly employed more expensive PM active samplers such as cascade impactors. The particles trapped in this way can then be easily analysed by means of Scanning Electron Microscopy coupled to Energy Dispersive Spectrometer (SEM-EDS), Micro Energy Dispersive X-Ray Fluorescence Spectrometry (μ-EDXRF) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). In the studied case, the Galleries of Punta Begoña, the identification of sulphates deposition add new ions to the building materials, the marine aerosol affects significantly to the reinforcement of the concrete and the important deposition of Fe particles may be responsible of triggering the sulphating process in this historical building. The PM passive sampler and the characterisation methodology proposed in this work can be extensively applied to other situations where PM characterisation is required. Graphical abstract: Image 1 Highlights: Cost effective passive sampler development for particulate matter quantification. Characterization of the particulate matter affecting the conservation state of Cultural Heritage. Particulate matter deposition quantification per area and time of building material. X-ray fluorescence characterization of particulate matter.